2009
DOI: 10.1007/s12040-009-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of low latitude ionospheric E-region irregularities linked with daytime VHF scintillations measured from Varanasi

Abstract: at low latitude station Varanasi (geographic lat. = 25 • 15 N; long. = 82 • 59 E; geomagnetic lat. = 14 • 55 N, long. = 154 • E, dip angle = 37.3 • , sub-ionospheric dip = 34 • ) have been analyzed to study the behaviour of ionospheric E-region irregularities during the active solar and magnetic periods. The autocorrelation functions, power spectral densities, signal de-correlation times are computed to study the temporal features of ionospheric E-region irregularities linked with daytime scintillations. Deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Low-latitude observations have also indicated a correlation between the occurrence of daytime scintillation and E sb (Huang 1978;Patel et al 2007Patel et al , 2009). Additionally, a few observations of scintillation in the range of GHz have been also investigated for low latitudes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Low-latitude observations have also indicated a correlation between the occurrence of daytime scintillation and E sb (Huang 1978;Patel et al 2007Patel et al , 2009). Additionally, a few observations of scintillation in the range of GHz have been also investigated for low latitudes.…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, daytime GHz scintillation studies attracted as much attention as nighttime scintillation studies, perhaps because daytime scintillation have a relatively lower rate of occurrence and milder nature (Patel et al 2009). For the most part, scintillations are generally believed to be associated with the F layer at night and the blanketing sporadic E (E sb ) layer during the day (Kumar et al 2007;Zou and Wang 2009;Zou 2011;Seif et al 2012;Alfonsi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for present computation we have taken a = 10 and b = 1. At our low latitude station Varanasi we are recording amplitude scintillations for the signal frequency 250 MHz from FLEETSAT satellite parked at 73°E Singh et al, 2004Singh et al, , 2006Patel et al, 2009). For this source, the distance between the source and the observation plane is 6.6R e and the zenith angle is $2.5°.…”
Section: Data Selection and Modeled Parametersmentioning
confidence: 99%
“…At a low latitude ground station, Varanasi the amplitude scintillations obtained are generally weak and moderate (Singh et al, 1993(Singh et al, , 2004(Singh et al, , 2006Patel et al, 2009). After analyzing scintillations recorded at low latitude station Varanasi, Singh et al (2006) showed that the power law index for irregularity are in the range of À2 to À8 with the mean value of À4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation